HTLV-1/-2 and HIV-1 co-infections: retroviral interference on host immune status - Pilotti, Elisabetta; Bianchi, Vittoria; De Maria, Andrea; Bozzano, Federica; Romanelli, Maria G.; Bertazzoni, Umberto; Casoli, Claudio (Frontiers in Microbiology, 2013)
The human retroviruses HIV-1 and HTLV-1/HTLV-2 share similar routes of transmission but cause significantly different diseases. In this review we have outlined the immune mediated mechanisms by which HTLVs affect HIV-1 disease in co-infected hosts. During co-infection with HIV-1, HTLV-2 modulates the cellular microenvironment favoring its own viability and inhibiting HIV-1 progression. This is achieved when the HTLV-2 proviral load is higher than that of HIV-1, and thanks to the ability of HTLV-2 to: i) up-regulate viral suppressive CCL3L1 chemokine expression; ii) overcome HIV-1 capacity to activate the JAK/STAT pathway; iii) reduce the activation of T and NK cells; iv) modulate the host miRNA profiles. These alterations of immune functions have been mainly attributed to the effects of the HTLV-2 regulatory protein Tax and suggest that HTLV-2 exerts a protective role against HIV-1 infection. Contrary to HIV-1/HTLV-2, the effect of HIV-1/HTLV-1 co-infection on immunological and pathological conditions is still controversial. There is evidence that indicate a worsening of HIV-1 infection, while other evidence does not show clinically relevant effects in HIV-positive people. Possible differences on innate immune mechanisms and a particularly impact on NK cells are becoming evident. The differences between the two HIV-1/HTLV-1 and HIV-1/HTLV-2 co-infections are highlighted and further discussed.